Pengaruh Simulasi Pertolongan Pertama terhadap Pengetahuan Remaja Karang Taruna tentang Fraktur di Desa Sri Rejo Agung - M. Faisal Firdaus; Dessy Hermawan; Eka Yudha Christanto (Universitas Nurul Jadid, 2026)
First aid in emergency cases, particularly fracture management, is an essential skill that should be mastered by the community, especially youth organizations such as Karang Taruna who are actively involved in social activities. However, their knowledge regarding fracture management remains relatively low. to analyze changes in knowledge before and after emergency first aid simulation on increasing the knowledge of youth in the Karang Taruna in managing fractures in Sri Rejo Agung Village, East Lampung 2025. This quantitative research used a pre-experimental design with a one-group pre-test and post-test approach. The sample consisted of 36 respondents selected using a total sampling technique. The research instrument was a questionnaire on knowledge about fracture management. Normality of difference scores was assessed before using paired sample t-test. The results showed a significant increase in the average knowledge score from 53.47 (pre-test) to 78.75 (post-test), with p = 0.000 (p < 0.05). This indicates a significant increase in knowledge after the simulation on enhancing adolescents’ knowledge. Simulation can be an effective educational method to improve adolescents’ understanding of fracture management. It is recommended that healthcare providers and community organizations adopt simulation as a routine learning strategy to strengthen emergency preparedness.